2009
DOI: 10.1016/j.bbagen.2009.03.032
|View full text |Cite
|
Sign up to set email alerts
|

In vivo calcium imaging of OFF-responding ASK chemosensory neurons in C. elegans

Abstract: BACKGROUND How neurons and neuronal circuits transform sensory input into behavior is not well understood. Because of its well-described, simple nervous system, Caenorhabditis elegans is an ideal model organism to study this issue. Transformation of sensory signals into neural activity is a crucial first step in the sensory-motor transformation pathway in an animal's nervous system. We examined the properties of chemosensory ASK neurons of C. elegans during sensory stimulation.METHOD A genetically encoded calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Desensitization may also enable processes such as novelty detection, acute protection from overstimulation, or sharpening of response dynamics for efficient downstream processing (Wark et al, 2007). Interestingly, desensitization is observed in other C. elegans sensory neurons whose calcium levels increase with stimulation, like AWA, but is less prominent in sensory neurons whose calcium levels decrease with stimulation, like AWC (Chalasani et al, 2007; Hilliard et al, 2004; Suzuki et al, 2008; Wakabayashi et al, 2009). The depolarizing regime of sensory processing may preferentially encode stimulus change over stimulus level, and may help explain why AWA and AWC, which detect similar and even overlapping attractive odors, have distinct sensory transduction properties.…”
Section: Discussionmentioning
confidence: 99%
“…Desensitization may also enable processes such as novelty detection, acute protection from overstimulation, or sharpening of response dynamics for efficient downstream processing (Wark et al, 2007). Interestingly, desensitization is observed in other C. elegans sensory neurons whose calcium levels increase with stimulation, like AWA, but is less prominent in sensory neurons whose calcium levels decrease with stimulation, like AWC (Chalasani et al, 2007; Hilliard et al, 2004; Suzuki et al, 2008; Wakabayashi et al, 2009). The depolarizing regime of sensory processing may preferentially encode stimulus change over stimulus level, and may help explain why AWA and AWC, which detect similar and even overlapping attractive odors, have distinct sensory transduction properties.…”
Section: Discussionmentioning
confidence: 99%
“…The AWB and ASK amphid chemosensory neurons ( Figure 1A) respond largely to volatile and aqueous compounds, including lipophilic pheromones, respectively (Bargmann and Horvitz 1991;Troemel et al 1997;Kim et al 2009;Macosko et al 2009;Wakabayashi et al 2009). We and others previously showed that the AWB neurons express a subset of predicted GPCRs encoded by the C. elegans genome (Troemel et al 1995;Colosimo et al 2004;Nokes et al 2009;C.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that ablating the AWC and ASK neurons partially disrupts the stimulatory effect of food on egg-laying (62). Ca 2+ imaging suggests that food-associated cues inhibit the AWC and ASK neurons (47). Perhaps the CO 2 -evoked Ca 2+ increases we observed in these same neurons antagonize the effects of food on ASK and AWC neurons, thereby inhibiting egg-laying.…”
Section: Resultsmentioning
confidence: 85%
“…cGMP channel subunits encoded by the tax-4 and tax-2 genes are expressed in four of the CO 2 -responsive neurons we have identified here: ASJ, ASK, AWC, and ASG. The previously studied sensory responses mediated by these neurons [e.g., ASJ responses to light (46); ASK responses to pheromones and food (45,47); and AWC responses to odors (48,49)] are disrupted in tax-2 or tax-4 mutants. Do CO 2 responses in these neurons also depend on these cGMP channels?…”
Section: Resultsmentioning
confidence: 99%